PREFERENSI INDIVIDU MUSLIM DALAM PENYALURAN ZAKAT, INFAK, SHADAQAH DAN WAQAF (ZISWA): KENDALA PEMBANGUNAN SEKTOR KETIGA - Kurniyati Indahsari (MediaTrend, 2013)
In a muslim dominated region, management of zakaf infaq, shadaqah, and waqf (ZISWA) is the third (community) sector activity which serves as an instrument to enhance people welfare. Unfortunately, the third sector development through the implementation of ZISWA instrument is constrained by the phenomenon of limited collected ZISWA funds in amil institution - a non profit organization as an actor in this sector. This phenomenological qualitative research showed that the phenomenon is caused by (1) the preference of ZISWA payers (donors) who tend to pay their ZISWA directly to the recipient; (2) the lack of some muslim awareness to pay their ZISWA; (3) limited financial owned by donors; and (4) the weaknesses of amil institution. The low level of trust towards amil institution is also a constraint of this sector development. It is suggested to do public socialization on the amil existence as well as what and how to accomplish ZISWA. In addition, the improvement of amil institutional governance is a must.